The influence of contents utility on students' use of social media - Ali, M. (Universiti Putra Malaysia, 2018)
The birth of the Internet has changed the processes of accessibility to information. A recent addition to this sphere is Web 2.0 applications which have transformed the entire landscape of information sharing in a multilateral fashion. This has provided people with an online platform to create access and interactions with others. These sites and apps are highly effective in learning and assist students in different academic interactions. However, students understand this sphere as a source of entertainment and social interactions. This attitude of students has transformed this platform into a source of distraction, which diverts their attention from effective learning and academic achievements. The earlier inquiries made into this particular area has formally disclosed that this web can augment student in learning and academic activities. Even so, less effort has been made to inquire the factors that can motivate students to harness this sphere for their academic excellence. The current study has been conducted with objectives to understand student adoption behaviour for this platform through site usefulness and information quality. Data was collected through a survey from undergraduate students from top five research universities in Malaysia and analysed with the help of SPSS Amos (Version 18). Applying technology acceptance models of Davis et al. (1989) and unified theory of acceptance and use of technology of Venkatesh et al. (2003) as a theoretical framework, the finding shows that site usefulness and information qualities significantly influence usage intention to use social media for academic purpose. However, information quality was found to be insignificant in encing the actual behaviour. Â© Universiti Putra Malaysia Press.